Analysis of the Effect of Blade Thickness on Propeller Water Turbine Performance Using Computational Fluid Dynamic - Fajar Paundra; Akhmad Nurdin; Hamid Abdillah; Puguh Elmiawan (VANOS Journal of Mechanical Engineering Education, 2022)
Hydropower on the lowest scale namely propeller pico-hydro, the turbine has a light workload so that allows it to be made from polymer materials with rapid manufacturing 3D printing technology.  In the design of the propeller turbine, the most concerned loading is the axial load which results in failure. A failure of designing the dimensions of the propeller turbine with polymer materials causes a fracture in the blades. This study aims to analyze how the effect of blade thickness on the performance of a propeller water turbine. Data collection in this study uses numerical simulation through computational fluid dynamics using SolidWorks Flow Simulation with the blade thickness variable used 1 mm to 3 mm with a fillet size 1.5 mm. Based on the results, the thickness of the blade affects the value of static torque. At a blade thickness of 2 mm, it shows the most optimal torque value compared to a thickness value below or above 2 mm.